2014
DOI: 10.1007/s00125-014-3290-0
|View full text |Cite
|
Sign up to set email alerts
|

A stress response pathway in mice upregulates somatostatin level and transcription in pancreatic delta cells through Gs and β-arrestin 1

Abstract: Aims/hypothesis Somatostatin secretion from islet delta cells plays an important role in regulating islet function and is tightly controlled by environmental changes. Activation of the adrenergic system promoted somatostatin secretion from islet delta cells; however, the role of the adrenergic system in regulating somatostatin content and transcription has not been defined. An imbalance between the somatostatin content and its secretion may cause dysfunctions in the islet delta cells. We have investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 37 publications
1
53
0
Order By: Relevance
“…However, although the insulin secretion of islets isolated from Sst-Cre +/-Cul4b fl/Y mice was still much lower than that of their WT littermates after SNX482 treatment, this difference was eliminated after nicardipine treatment ( Figure 3D). These data are in agreement with the observed somatostatin secretion patterns and reinforce the conclusion that L-type calcium channels in pancreatic δ cells are key components mediating the increased somatostatin secretion and impaired glucose metabolism in Sst In addition to intracellular calcium, the second messenger cAMP, the G q -PLC pathway, and kinase signaling are actively involved in hormone secretion from pancreatic islets (5,13,(39)(40)(41). Therefore, we preincubated the islets with several inhibitors, including cAMP-PKA signaling inhibitors Rp-CAMPs and H89, G q -PLC inhibitor U73122, MEK inhibitor U0126, and adenyl cyclase (AC) inhibitor 2′,5′-dideoxyadenosine (DDA), and we examined glucose-induced somatostatin secretion patterns ciency in the pancreatic β cells of Ins2-Cre +/-Cul4b fl/Y mice did not significantly affect insulin and somatostatin secretion levels in response to high glucose relative to trends found for Ins2-Cre +/-mice (Supplemental Figure 3, A and B).…”
Section: Cul4b Ablation In Pancreatic δ Cells Other Than β Cells Caussupporting
confidence: 89%
See 2 more Smart Citations
“…However, although the insulin secretion of islets isolated from Sst-Cre +/-Cul4b fl/Y mice was still much lower than that of their WT littermates after SNX482 treatment, this difference was eliminated after nicardipine treatment ( Figure 3D). These data are in agreement with the observed somatostatin secretion patterns and reinforce the conclusion that L-type calcium channels in pancreatic δ cells are key components mediating the increased somatostatin secretion and impaired glucose metabolism in Sst In addition to intracellular calcium, the second messenger cAMP, the G q -PLC pathway, and kinase signaling are actively involved in hormone secretion from pancreatic islets (5,13,(39)(40)(41). Therefore, we preincubated the islets with several inhibitors, including cAMP-PKA signaling inhibitors Rp-CAMPs and H89, G q -PLC inhibitor U73122, MEK inhibitor U0126, and adenyl cyclase (AC) inhibitor 2′,5′-dideoxyadenosine (DDA), and we examined glucose-induced somatostatin secretion patterns ciency in the pancreatic β cells of Ins2-Cre +/-Cul4b fl/Y mice did not significantly affect insulin and somatostatin secretion levels in response to high glucose relative to trends found for Ins2-Cre +/-mice (Supplemental Figure 3, A and B).…”
Section: Cul4b Ablation In Pancreatic δ Cells Other Than β Cells Caussupporting
confidence: 89%
“…L-type calcium channels are responsible for the influx of extracellular calcium during hormone secretion. We therefore measured high glucose-and high potassium-induced calcium signals in iso- In addition to intracellular calcium, the second messenger cAMP, the G q -PLC pathway, and kinase signaling are actively involved in hormone secretion from pancreatic islets (5,13,(39)(40)(41). Therefore, we preincubated the islets with several inhibitors, including cAMP-PKA signaling inhibitors Rp-CAMPs and H89, G q -PLC inhibitor U73122, MEK inhibitor U0126, and adenyl cyclase (AC) inhibitor 2′,5′-dideoxyadenosine (DDA), and we examined glucose-induced somatostatin secretion patterns ciency in the pancreatic β cells of Ins2-Cre +/-Cul4b fl/Y mice did not significantly affect insulin and somatostatin secretion levels in response to high glucose relative to trends found for Ins2-Cre +/-mice (Supplemental Figure 3, A and B).…”
Section: The Journal Of Clinical Investigation R E S E a R C H A R T mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a systematic examination of an agonist-induced interaction of FFA4 receptor with different G proteins, GRK or arrestin subtypes and their downstream functions is required. Recently, biophysical and pharmacological studies have revealed that for the same receptor, different ligands could induce significantly different conformations that selectively stimulated the activation of one of the downstream effectors of GPCRs and result in biased signaling (Shenoy and Lefkowitz, 2011;Whalen et al, 2011;Shukla et al, 2014;Strachan et al, 2014;Wang et al, 2014). For example, a β-arrestin2 biased downstream signaling of FFA4 receptor may maintain its beneficial effect in anti-inflammation but decrease its potential for promoting tumor growth and angiogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…G-protein- and β-arrestin–mediated signaling are the two main pathways underlying β2AR function (17,2729). Application of the protein kinase A (PKA) inhibitor (E)-N-(2-(4-bromocinna-mylamino)ethyl)isoquinoline-5-sulfonamide dihydrochloride (H89) significantly reduced, but did not eliminate, the formoterol-induced lactate release in U251 cells, demonstrating the contribution of Gs-PKA–mediated β2AR signaling in lactate release (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%